Glycosylation of Zein Hydrolysate as a Nanocarrier for Lutein Delivery: Preparation and Stability - Han, He; Jiao, Yan; Chang, Ying; Cheng, Yue; Shi, Lei (Frontiers in Pharmacology, 2022)
Lutein is a functional carotenoid that has a wide range of physiological benefits in humans. However, it easily degrades and becomes inactivated during storage and processing, resulting in low bioavailability. The development of new nanocarriers can effectively improve the stability and biological activity of lutein. In this study, zein hydrolysate (ZH) carriers were glycosylated with glucosamine (GLU) under the action of transglutaminase, and lutein-loaded glycosylated ZH nanoparticles (GZH-LUT) were constructed by liquid–liquid dispersion. The results showed that the GZH-LUT particles had a narrow size distribution in the range of 200~300 nm and a decreased zeta potential and polydispersity index. In particular, GZH trapped lutein more efficiently than ZH. In addition, GZH-LUT had better physical and chemical properties, including better water solubility, oxidative stability, and environmental stability than free lutein and ZH-LUT. These results indicate that glycosylated zein hydrolysate has the potential to be used as a novel protein-based nanocarrier to enhance the solubility and stability of lutein, which can further improve its bioavailability.